Uji Suspensi Kitosan untuk Mengendalikan Rayap (Coptotermes curvignathus Holmgren) pada Tanaman Karet di Lapangan - Mangaraja Lumban Gaol; Syahrial Oemry; Yuswani Pangestiningsih (Jurnal Agroekoteknologi, 2015)
The aim of the research was to get effective concentration of chitosan suspension to controltermites (Coptotermes curvignathus) on the rubber plants in the field. This research was conductedin experiment field at Sungei Putih Research Centre since March until June 2014. This researchused Randomized Block Design Non Factorial with 6 treatments, 0, 6, 12, 18, 24 and 30 g whichapplicated with bait and three replications. The result showed that the highest percentage (100%)of termites mortality was 18 g treatment and the lowest (18.67%) at control treatment five day afterapplication. The symptoms infection of chitosan was characterized by discoloration of the abdomenwhich beginning white to blackish brown.Keywords : termites, chitosan, bait